Analysis of Inflation Dynamics and Economic Growth in Post-Pandemic Indonesia: An Islamic Economics Perspective - M. Hidayat; Muhammad Irwan Padli Nasution; Muhammad Habibi Siregar (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: This study aims to analyze the dynamics of inflation and economic growth in Indonesia during the post-pandemic period (2019–2024) by integrating conventional macroeconomic and Islamic economic perspectives. Method: The research employs a quantitative approach using regression and descriptive analysis based on secondary time-series data obtained from Bank Indonesia, BPS, the World Bank, and the IMF. The variables analyzed include inflation, economic growth, money supply, interest rates, government expenditure, tax revenue, exchange rates, and stock market indices. Results: The results indicate that the relationship between inflation and economic growth is complex and non-linear. Moderate inflation is found to stimulate economic growth, particularly during the post-pandemic recovery phase, whereas high inflation tends to hinder growth in the long run. Additionally, the growth of money supply has a significant impact on inflation, which in turn negatively affects economic growth, reflecting a trade-off between monetary expansion and economic stability. Conclusion: The findings also show that maintaining inflation stability within the range of 2–3% is crucial for sustaining economic growth. From an Islamic economic perspective, inflation control is not only aimed at maintaining macroeconomic stability but also at achieving distributive justice and social welfare in line with the principles of maqashid al-shariah. Therefore, optimal economic policy should integrate economic efficiency with the values of justice and balance to create a sustainable economic system.